Analisis Pengaruh Penerimaan Aplikasi E-Commerce Menggunakan Multigroup-Partial Least Square (MGA-PLS) - Gita Yantika Sari; Marizsa Herlina (Bandung Conference Series: Statistics, 2022)
Abstract. The existence of technology has affected society and the surrounding environment, because technology can help in various things such as improving the economy. In the economic field, technological developments can be in the form of the development of the financial system used, for example electronic commerce or better known as Electronic Commerce/E-Commerce. After the Covid-19 outbreak, the development of E-Commerce began to increase because it could reduce the spread of the epidemic, until it began to develop in rural areas. Technology Acceptance Model (TAM) is one of the models built to analyze and understand the factors that influence the acceptance of the use of computer technology. In addition, in understanding the factors that influence the acceptance of the use of computer technology, Multigroup Structural Equation Model analysis with Partial Least Square (MGA-PLS) is used which aims to predict and analyze determinant factors in measuring the influence of independent variables on the dependent variable and to find out whether or not there is a difference in influence between two or more groups/groups. Based on the analysis, the factors that influence user interest in accepting E-Commerce applications among the people of Karangsari Village, Garut Regency are Perceived Usefulness, Trust, and Attitude Towards Using. In addition, by using Multigroup analysis, it can be concluded that there is no difference in the effect on the income group, which means that the views or responses of the respondents of each income group to the factors that influence the acceptance of E-Commerce applications are the same. Abstrak. Keberadaan teknologi telah mempengaruhi masyarakat dan lingkungan sekitar, karena teknologi dapat membantu dalam berbagai hal seperti memperbaiki ekonomi. Dalam bidang ekonomi perkembangan teknologi dapat berupa perkembangan sistem keuangan yang digunakan, contohnya perdagangan elektronik atau lebih dikenal dengan istilah Electronic Commerce/E-Commerce. Setelah adanya wabah Covid-19, perkembangan E-Commerce mulai meningkat karena dapat mengurangi penyebaran wabah, hingga hal tersebut pun mulai berkembang di pedesaan. Technology Acceptance Model (TAM) adalah salah satu model yang dibangun untuk menganalisis dan memahami faktor-faktor yang mempengaruhi diterimanya penggunaan teknologi komputer. Selain itu, dalam memahami faktor-faktor yang mempengaruhi diterimanya penggunaan teknologi komputer tersebut digunakan analisis Multigroup Structural Equation Model dengan Partial Least Square (MGA-PLS) yang bertujuan untuk memprediksi maupun analisis faktor determinan dalam mengukur besarnya pengaruh variabel bebas terhadap variabel terikat serta untuk mengetahui ada atau tidaknya perbedaan pengaruh antara dua atau lebih kelompok/grup. Berdasarkan analisis diperoleh faktor-faktor yang mempengaruhi minat pengguna dalam penerimaan aplikasi E-Commerce di kalangan masyarakat Desa Karangsari Kabupaten Garut adalah Perceived Usefulness (Kegunaan/Manfaat), Kepercayaan, dan Attitude Towards Using (Sikap Terhadap Penggunaan). Selain itu, dengan menggunakan analisis Multigroup didapat kesimpulan bahwa tidak ada perbedaan pengaruh pada kelompok pendapatan yang artinya pandangan atau tanggapan responden setiap kelompok pendapatan terhadap faktor yang menjadi pengaruh dalam penerimaan aplikasi E-Commerce adalah sama.